If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 15x + 24 = 139 Reorder the terms: 24 + 15x = 139 Solving 24 + 15x = 139 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-24' to each side of the equation. 24 + -24 + 15x = 139 + -24 Combine like terms: 24 + -24 = 0 0 + 15x = 139 + -24 15x = 139 + -24 Combine like terms: 139 + -24 = 115 15x = 115 Divide each side by '15'. x = 7.666666667 Simplifying x = 7.666666667
| Y=0.0987x+8.1883 | | (x^2d^2-3xd+2i)y=0 | | 1x-3-5x=-27 | | 6x-9x=11x | | 5+6x=4x+10 | | y=0.50x/111 | | 81r^2-5=59 | | 0=3W-8-35 | | 2.5(2)-0.2y=8.1 | | 25x^5-50x^4-x+2=0 | | y=0.50(111)+16 | | x^2-4x-14-x=0 | | 5=7(1)-y | | 7(x-1)+8=5x+2(1+x) | | 14xy-7x+15y-13xy= | | y=-5/6(2)+5 | | -a-3=-2a-3 | | -2/5x-99/10 | | 14y-9-8y-6= | | 6x-10(0)+2=0 | | y=0.50(50)+16 | | 6x-10(2)+2=0 | | 8d-23+d=42 | | y=0.50(100)+16 | | pq-7q+4p-9pq+2q= | | 4x^2+5y^2+16x+10y-79=0 | | 0.6-3.8=0.4 | | 9k+12s-14s+6k-3s= | | -3(t-4)+6t=7t-2 | | y=-0.80(55)+139 | | 2W+1=45 | | y=-0.80(45)+139 |